Serum Level of IL -6, CRP and PCT among Food Handlers Patient Infected with Helicobacter Pylori - Mahmood, Qusay S.; Jafer, Nehan Bahaaldden; Abass, Sahlah KH. (American Journal of Biology and Natural Sciences, 2026)
The current study aimed at determining the prevalence of Helicobacter pylori in food handlers and the effect of the infection on the choice of serum and hematological parameters. The empirical work was done in the laboratories of Kirkuk Teaching Hospital, and it was conducted during the period between November 7, 2022, and March 28, 2023. The researchers used a sample of 150 food handlers including personnel of restaurants and cafes. The samples were also stratified into two cohorts. The first group was 45 persons who were diagnosed to have been colonized by the above bacterial pathogen, and the second group was a control group of 20 persons as part of the experimental set-up. The highest level of infection was observed in the age group of 20-30 years. Diagnostic tests were conducted using the following bacterial tests: Urea Breath Test (UBT), Stool Antigen Test (SAT), and the Antibody Test in Serum (ATS). The highest rate of symptoms was found among those infected with H. pylori was associated with loss of appetite (53.3%), followed by dyspepsia (44.45%), stomach pain (31.1%), and gastroesophageal reflux disease (20%). The least common symptom was gastritis (15.5%). The studied criteria included a set of immunological tests, where the levels of high sensitivity C-reactive protein (HSCP), procalcitonin, and interleukin6 (IL- 6) were measured. This was found to differ statistically significantly (P<0.01) between the level of the serum of both high-sensitivity C-reactive protein (HSCP) and procalcitonin in infected patients compared to the control cohort. Moreover, the results showed a strong rise (P<0.01) in the serum levels of IL 6 in the infected group.